Preventing Thrombosis in Cancer Patients - Budi Setiawan; Eko Adhi Pangarsa; Damai Santosa; Ridho M Naibaho; Rahajuningsih Dharma Setiabudy; Catharina Suharti (Acta Medica Indonesiana)
Thromboembolism events, either venous (VTE) or arterial thromboembolism (ATE) remain a highly prevalent complication in cancer patients. Thrombosis is a leading cause of death, contributor to significant morbidity, the reason of delayed cancer treatment, leading to increased cancer financing and expenses. Both cancer and its treatment are recently found to be related to vascular inflammation through the induction of tissue factor (TF) expression and promoting a procoagulant state which triggers the activation of coagulation system. Several risk factors may also coexist such as dehydration, immobilization, smoking, obesity, previous DVT, etc. Even in patients with asymptomatic deep vein thrombosis (DVT), they have a three-fold increase in mortality. The high morbidity and mortality of VTE raises the need for thromboprophylaxis to reduce the incidence of overt thrombosis, albeit against its possible side effects related to anticoagulant prescription. This article highlighted the clinical perspectives for thromboprophylaxis while counting on the risk stratification in a particular cancer patient.